Aplicações da espectrometria de massas de resssonância ciclotrônica de íons por transfromada de Fourier (FT-ICR MS) em petroleômica - Pereira, Thieres Magaive Costa (2013)
Petroleum is a complex mixture, being one of the most challenging mixtures for chemical analyzes. Many techniques are employed to characterize constituents of the oil. However , when we combine the highest resolving power and accuracy of mass spectrometry , especially Ion Cyclotron Resonance Fourier Transform ( FT - ICR MS ) with sources of atmospheric pressure ionization , an assignment need more than 20 000 organic compounds in the oil can be obtained. In the oil industry there is a great interest in the analysis of asphaltenes and naphthenic acids due to problems such as corrosion and deposit formation, which increases production costs. Therefore this study aims to evaluate the thermodegradation of naphthenic acids, besides the use of sources of ESI, APCI, APPI, MALDI and LDI for the acquisition of new data on the characterization of asphaltenes . Two test oils were used in thermodegradation of the oil with an acidity of 2.38 mg KOH g -1 and Oil B with 4.79 mg KOH g- 1 which were treated at 280 , 300 and 350 ° C for a period of 2 , 4 and 6 hours. Generally, the major classes identified for both samples O2, NO2, and C, respectively. A slight reduction of NAT and relative abundance refers to the class O2 were observed as a function of temperature and aging time (T = 280 ? 300 ° C t = 2 ? 6 h), and the heat treatment temperature at 350 ° C showed a determinant for the removal of class O2. The chemical asphaltenes Brazilian samples was evaluated using five different methods of ionization in both modes of ionization: positive and negative, then the molecular weight distribution, distribution class, typical plots versus carbon number and DBE van Krevelen diagrams were obtained and discussed. An unusual behavior was observed for the LDI and MALDI source ( ± ) FT - ICR MS . A comprehensive profile of m / z 500-3000, with spacing of 24 Da was observed, and this corresponds to allotropes of fullerene C60. In general, the asphaltenes had an heteroatómicas high proportion of species such as HC , HC [ H] , N, [ H] , N2O N2O [ H] N2, N2 [ M ] O O [ H] to mode (+) and N, [ H ] , NO [ H] , NO , NO2, [ H] , N2O N2O [ H ] for the negative mode . In the diagrams DBE against the carbon number , the asphaltenes shown for each value of DBE composed of a small amplitude with respect to NC, thus providing images that form a line of 45 ° between the axes CN and DBE. This indicates that these compounds do not exhibit large chain alkyl, composed mainly of aromatic rings. In general diagrams van Krevelen showed a high proportion of compounds ratio H / C ~ 0.7, confirming the existence of highly aromatic species